Effect of December 2014 great flood on the physico-chemical properties of the soils in the Kelantan Plains, Malaysia - Jusop, Shamsuddin; Panhwar, Qurban Ali; Othman, Radziah; Ismail, Roslan; Jol, Hamdan; Yusoff, Melissa Alina (Scientific Research Publishing, 2016)
Heavy rain falling on land at the upper reaches of the Kelantan River, Malaysia, on December 2014, had resulted in severe soil erosion and untold damages to croplands. The lower reaches of the river were heavily silted with infertile materials considered unfit for crop production. A study was conducted to explain why the flood phenomenon occurred, to determine the physico-chemical properties of the sediments silted in the Kelantan Plains and to propose measures for soil mitigation. Results showed that the silted sediments were characterized by the presence of quarts, mica, feldspars, kaolinite, gibbsite and hematite believed to come from the top- and subsoil of the upland areas. The sediments’ pH was very low and Al and/or Fe contents were very high, while nitrogen and carbon contents varied from area to area. Soils in the Kelantan Plains badly affected by this great flood needed to undergo proper ameliorative program. The most appropriate measure would be to apply ground magnesium limestone in combination with bio-fertilizer fortified with beneficial microbes that would increase their pH to a level above 5, which consequently eliminates Al3+ and/or Fe2+ that causes toxicity to the crops growing on them. The organic material so added would enhance the formation of soil structures. It is advised that the farming communities in the upper reaches of the Kelantan River would have to follow the advice advocated by the Department of Agriculture, Peninsular Malaysia, via MyGAP initiative, in order to sustain agricultural production on their land.